A comprehensive comparison of dye-sensitized NiO photocathodes for solar energy conversion. Issue 16 (6th January 2016) - Wood, Christopher J.; Summers, Gareth H.; Clark, Charlotte A.; Kaeffer, Nicolas; Braeutigam, Maximilian; Carbone, Lea Roberta; D'Amario, Luca; Fan, Ke; Farré, Yoann; Narbey, Stéphanie; Oswald, Frédéric; Stevens, Lee A.; et al.
Abstract : Summary of photocurrent vs. time and (inset) total theoretical H2 generated for the 7 different NiO electrodes compared in this study. Abstract : We investigated a range of different mesoporous NiO electrodes prepared by different research groups and private firms in Europe to determine the parameters which influence good quality photoelectrochemical devices. This benchmarking study aims to solve some of the discrepancies in the literature regarding the performance of p-DSCs due to differences in the quality of the device fabrication. The information obtained will lay the foundation for future photocatalytic systems based on sensitized NiO so that new dyes and catalysts can be tested with a standardized material. The textural and electrochemical properties of the semiconducting material are key to the performance of photocathodes. We found that both commercial and non-commercial NiO gave promising solar cell and water-splitting devices. The NiO samples which had the two highest solar cell efficiency (0.145% and 0.089%) also gave the best overall theoretical H2 conversion.